An Effective Fast Searching Algorithm for Internet Crawling Usage - Chia, Zhen Hon; Nor Azhar, Ahmad (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
The search algorithm is a crucial part in any internet applications. One of the crucial usages is internet crawling to find the best information using keywords. The searching algorithm has been one of the famous algorithm which is used throughout most of the existing software, such as Google, Facebook, Twitter. Therefore, an effective search algorithm is very crucial as most of the users are depending on it. This project will benefit to all users. The prototype has been developed using PHP, JavaScript enveloped in a Bootstrap web creator. It has been tested in eBook searching for UMP Library and produced success story. It could search faster in comparison to the other approach when crawling more than 10k eBook titles and content. Further development could be a combination of a faster method inside the proposed searching engine.